Integrasi Manajemen Berbasis Sekolah dan Budaya Lokal: Inovasi Penguatan Lembaga Pendidikan Islam di Kabupaten Bone - Dwiyama, Fajri (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2025)
This article examines the innovation of integrating School-Based Management (SBM) with local culture as a strategy to strengthen Islamic educational institutions in Bone Regency. This study aims to analyze how the values of Bone's local wisdom, such as the principles of "siri' na pacce" (self-esteem and solidarity), "mappatabe" (manners), and the "pangngadereng" (customary governance) system, can be adapted within the framework of MBS to create a contextual and sustainable education management model. The research method uses a qualitative approach with case studies in three selected madrasas and pesantren, through in-depth interviews, participatory observations, and document analysis. The findings of the study show that the integration of MBS-local culture not only increases community participation in educational decision-making, but also strengthens Islamic identity that is in harmony with local wisdom. This innovation is reflected in the culture-based curriculum, strengthening the role of indigenous leaders in school committees, and the implementation of an evaluation system that combines national standards and local values. This article offers a new perspective in Islamic education management by emphasizing the importance of glocalization (global-local) in facing the challenges of modernization, while recommending a collaborative model between governments, educational institutions, and indigenous stakeholders to achieve a holistic educational transformation. These findings make a theoretical contribution to the development of culture-based education management as well as practical implications for the strengthening of Islamic educational institutions in areas with similar socio-cultural characteristics.